2020
DOI: 10.1021/acs.jproteome.0c00237
|View full text |Cite
|
Sign up to set email alerts
|

Deep Proteome Profiling of Semen of Indian Indigenous Malnad Gidda (Bos indicus) Cattle

Abstract: Malnad Gidda is a dwarf indigenous cattle breed of India, which is known for its uniqueness of calving every year under a low input grazing system of rearing. Bulls of Malnad Gidda are known to be highly fertile even in stress conditions. However, the proteomic profiling of semen of this breed has not been investigated so far, which might provide a platform for a better understanding of its semen quality and male fertility. Therefore, we made an effort to characterize and quantify the proteome of seminal plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Since bovids and cetaceans are evolutionarily related (Vislobokova, 2013), belonging to the order Cetartiodactyla, a bovine dataset (Ramesha et al, 2020) was compared with dolphin. In addition, human as a biological model (Batruch et al, 2011;Baker et al, 2013;Amaral et al, 2014) and dogs (canids) (Aquino-Cortez et al, 2017;Araujo et al, 2020), because their only accessory sex gland is the prostate, as in dolphins, were also included in the comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Since bovids and cetaceans are evolutionarily related (Vislobokova, 2013), belonging to the order Cetartiodactyla, a bovine dataset (Ramesha et al, 2020) was compared with dolphin. In addition, human as a biological model (Batruch et al, 2011;Baker et al, 2013;Amaral et al, 2014) and dogs (canids) (Aquino-Cortez et al, 2017;Araujo et al, 2020), because their only accessory sex gland is the prostate, as in dolphins, were also included in the comparison.…”
Section: Resultsmentioning
confidence: 99%
“…In Fer1l5-FLAG or Fer1l5-PA Tg mice, we detected FER1L5-FLAG or FER1L5-PA using large amounts of testicular proteins, which hamper the analysis of FER1L5 localization. Therefore, we cannot rule out the possibility that FER1L5 plays roles in the testes and impaired acrosome reaction in Fer1l5 mutant mice is a consequence of defective spermatogenesis; however, previous proteomics analysis showed that mature spermatozoa contained FER1L5 in several mammalian species such as humans ( 36 ), cattle ( 37 ), yaks ( 38 ), and rams ( 39 ). Furthermore, our mass spectrometry (MS) analyses detected FER1L5 peptides in mouse mature spermatozoa (fig.…”
Section: Discussionmentioning
confidence: 96%
“…Among the various members of SPATA family, we found abundance of SPATA19 in low‐fertile bull. SPATA19 is located on sperm mitochondrial outer membrane and involved in regulation of cell differentiation and sperm development (Ramesha et al, 2020; Suzuki‐Toyota et al, 2007). Earlier, its expression was reported in the testicular tissue and haploid spermatid (Doiguchi et al, 2002; Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%